Cerebral microbleeds and the risk of intracerebral haemorrhage after thrombolysis for acute ischaemic stroke: systematic review and meta-analysis. Issue 3 (28th September 2012) - Charidimou, Andreas; Kakar, Puneet; Fox, Zoe; Werring, David J
Abstract : Background: Intracerebral haemorrhage (ICH) remains the most devastating yet unpredictable complication of intravenous thrombolysis for acute ischaemic stroke. We performed a systematic review and meta-analysis, to assess whether the presence of cerebral microbleeds (CMBs) on prethrombolysis MRI scans is associated with an increased risk of ICH. Methods: We searched PubMed for studies assessing ICH risk in patients with acute ischaemic stroke treated with thrombolysis, in relation to the presence of pre-treatment CMBs. Results: We identified five studies including 790 patients and pooled data in a meta-analysis. The CMB (+) versus CMB (−) groups were not significantly different in age, gender or stroke severity. The overall prevalence of CMBs was 135/790 (17.1%). Amongst patients with CMBs, 10/135 (7.4%) experienced a symptomatic ICH after thrombolysis, compared to 29/655 (4.4%) patients without CMBs. The pooled relative risk of ICH was 1.90 (95% CI 0.92 to 3.93; p=0.082). Conclusions: The available evidence does not demonstrate a statistically significant increased risk of symptomatic ICH after thrombolysis for ischaemic stroke in patients with CMBs. However, in view of the methodological limitations of the studies included, the clinical relevance of any potential hazard associated with CMBs remains uncertain. Further studies are warranted to evaluate whether the risk of ICH might outweigh the benefit of thrombolysis, especially in patients with multiple lobar CMBs suggestive of cerebral amyloid angiopathy.